Modelling the simple shear behaviour of clay considering principal stress rotation. (January 2020) - Lu, Nan; Yang, Yunming; Yu, Hai-Sui; Wang, Zhe
Highlights: A simple model for clay simple shear modelling is proposed. The model considers the effect of principal stress axes rotation. Undrained shear strength of clays is satisfactorily captured. Non-coaxial behaviour is also well reproduced. Abstract: Simple shear deformation is prevailing in geotechnical problems. One of its salient features is the rotation of the principal stress axes. Early numerical modelling of soil simple shear behaviour usually neglects the plastic deformation induced by principal stress rotation. Recent attempts at accurately modelling the sand simple shear behaviour have accounted for this loading mechanism, but those for the clay simple shear modelling are rare. To fill the gap, this paper presents a simple constitutive model for the simulation of clay simple shear behaviour with consideration of the effect of the principal stress rotation. The model uses a non-associative flow rule and incorporates an additional mechanism associated with the principal stress rotation. The new mechanism caters for the soil non-coaxiality and plastic volumetric response under pure rotation of principal stress axes. Stress–strain incremental linearity is maintained in the proposed model. Comparisons of simulations with clay simple shear test data justify the importance of the principal stress rotation. The model satisfactorily captures the undrained shear strength. The soil non-coaxial behaviour is also well reproduced.